Swedish Wikipedia - Språkbanken Text (University of Gothenburg, 2024)
Corpus of Swedish Wikipedia

Korpus av svenskspråkiga Wikipedia
Svenska Wikipedia
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik